Join IDNLearn.com and become part of a knowledge-sharing community that thrives on curiosity. Ask your questions and receive accurate, in-depth answers from our knowledgeable community members.

Solve by substitution.
x + 3y = -2
1-3x + y = 6


Sagot :

Explanation:
3
x
+
y
=
2

x

3
y
=
6


6

3
y
=
x
Substitute this equation into the other system wherever you see
x
.
3
(

6

3
y
)
+
y
=
6
Distribute
3
onto
(

6

3
y
)

18

9
y
+
y
=
2
Combine alike terms

8
y
=
20
Divide to solve for
y

8
y

8
=
20

8

y
=

20
8
Then solve for
x
using the value of
y
.

x

60
8
=
6
x
=

108
8
y
=

20
8